Pembelajaran Matematika Berbasis Komputer Untuk MGMP Matematika SMP Di Kabupaten Pangkajene dan Kepulauan - Haryanto, Loeky; Mahie, Andi Galsan; Amir, Amir Kamal; Aris, Naimah; Kasbawati, Kasbawati (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
Computers as learning media have become mandatory in the teaching and learning process. Mathematical learning in which the field of study is abstract and requires logical thinking is also inseparable from computer learning media. Many software made to facilitate mathematics learning activities, among others: Geogebra, Microsoft Mathematic, Maple, Matlab, SAS, SPSS etc. The dedication activities have been carried out by the Mathematics Department of FMIPA in collaboration with the Hasanuddin University Research and Community Service Institute (Lp2M) in Mathematics Subject Teacher (MGMP) at the junior high School in Pangkajene and Kepulauan District (Pangkep) held in the Junior High School 4 hall with a number of participants as many as 30 teachers from 23 various junior high schools in Pangkep Regency who are members of the MGMP. The purpose of this activity is to improve the ability of junior high school mathematics teachers in Pangkep Regency to use computer-based learning media such as Maple and Matlab. The material provided was training on Maple and Matlab software to support mathematics learning. The results of this activity can improve the ability of mathematics teachers to master mathematical material assisted by software.